THE TRANSFORMATION OF CORRESPONDENCE EDUCATION TO DISTANCE EDUCATION IN NIGERIA, 1927-1987 (1992)
This study examined the transformation of correspondence education to distance education in Nigeria, from 1927 to 1987. This was against the background of the transformation of the novel system of instruction in many other parts of the world. Investigations have shown the extreme attachment of the system in Nigeria to the old methods and media of instruction. This is in spite of the long history of correspondence education in Nigeria, where its first alumnus took his degree in 1927. Yet the prevalent use of the, term distance education to describe practices in the field gives the impression that there has indeed been a transformation. This study was thus carried out to examine the extent to which transformation has taken place. The historical approach was adopted in which an extensive study of archival materials and documents was carried out. Interviews were conducted with alumni, present students of the system and practitioners alike. The study identified a number of periods in the transformation process. These are: i. the period of external examinations and foreign correspondence colleges; ii. the period of local initiatives and entrepreneurship in correspondence education; iii. the period of university involvement; and iv. the transformation period in embryo. These four periods exposed the gradual transformation of the methods, the media, support services, two-way communication system, courses in and clientele of correspondence education, thus paving the way for the emergence of distance education. Some of the findings of the study are: i. the foundations for the transformation of correspondence education to distance education have not been totally laid; ii. most of the institutional providers of correspondence education in Nigeria are not fully committed to the promotion of its transformation; the impact of an increased iii. number of radio and television stations in the country, or of the satellite and computer systems has not been fully felt in the transformation process. In view of the above, the researcher recommends the following, among others: i. the need for more government involvement in the funding and quality control of distance education systems in Nigeria; ii. the need for distance education institutions to have policies on development aimed at further bridging, the distance between them and their clientele; iii. the need to make existing structures which signify media development in the country relevant to media growth in distance education.